Guideline-Adherent Clinical Validation of a Comprehensive 170-Gene DNA/RNA Panel for Determination of Small Variants, Copy Number Variations, Splice Variants, and Fusions on a Next-Generation Sequencing Platform in the CLIA Setting - Boyle, Theresa A.; Mondal, Ashis K.; Saeed-Vafa, Daryoush; Ananth, Sudha; Ahluwalia, Pankaj; Kothapalli, Ravi; Chaubey, Alka; Roberts, Evans; Qin, Dahui; Magliocco, Anthony M.; Rojiani, Amyn M.; Kolhe, Ravindra (Frontiers in Genetics, 2021)
We describe clinical validation of a targeted DNA and RNA-based next-generation sequencing (NGS) assay at two clinical molecular diagnostic laboratories. This assay employs simultaneous DNA and RNA analysis of all coding exons to detect small variants (single-nucleotide variants, insertions, and deletions) in 148 genes, amplifications in 59 genes, and fusions and splice variants in 55 genes. During independent validations at two sites, 234 individual specimens were tested, including clinical formalin-fixed, paraffin-embedded (FFPE) tumor specimens, reference material, and cell lines. Samples were prepared using the Illumina TruSight Tumor 170 (TST170) kit, sequenced with Illumina sequencers, and the data was analyzed using the TruSight Tumor 170 App. At both sites, TST170 had ≥ 98% success for ≥ 250X depth for ≥ 95% of covered positions. Variant calling was accurate and reproducible at allele frequencies ≥ 5%. Limit of detection studies determined that inputs of ≥50 ng of DNA (with ≥ 3.3 ng/ul) and ≥ 50 ng RNA (minimum of 7 copies/ng) were optimal for high analytical sensitivity. TST170 assay results were highly concordant with prior results using different methods across all variant categories. Optimization of nucleic acid extraction and DNA shearing, and quality control following library preparation is recommended to maximize assay success rates. In summary, we describe validation of comprehensive and simultaneous DNA and RNA-based NGS testing using TST170 at two clinical sites.